Bola Benih Sebagai Kiat Baru dalam Rehabilitasi Hutan dan Lahan Kritis di Kecamatan Tinggimoncong, Sulawesi Selatan - Muh. Restu; Syamsuddin Millang; Samuel Paembonan; Budirman Bachtiar; Gusmiaty Gusmiaty (Biocelebes, 2012)
Rehabilitate forest and farm critical must special attention and need of the new method that more practical, quick, and cheap. Method of seed ball is its alternative method. with consideration referred, then this research bent on for (1) know seed amount every seed ball that give percentage grows and plants growth sengon the best (2) know size of seed ball diameter the best to percentage grow and plants growth sengon; (3) know appropriate type of farm closing to percentage grow and plants growth sengon; (4) know interaction influence between seed amount every ball, level of seed ball, type of the best farm closing to percentage grow and plants growth sengon at the site. This research is executed start month September 2012 up to final December 2012 in district Tinggimoncong Gowa Regency. this research uses random design complete pattern factorial that consisted of 3 factor that is seed amounts every seed ball as first factor with 4 levels that is 5 seeds, 7 seeds, 9 seeds, and 11 seeds every seed ball, second that is large size factor its diameter of seed ball that consisted of 4 levels that is 2.5 cm, 4 cm, 5.5 cm, and 7 cm, third factor that is farm closing that consisted of 4 levels that is opened (grass), coppice, beams, and cleaned (disc with diameter 20 cm). The three of this treatment factor are combined until got counted 4 x 4 x 4 = 64 treatment units. Every treatment unit consisted of 3 seed balls and repeated 3 times until required 64 x 3 x 3 = 576 seed balls. Variable that perceived is time starts germinate and percentage germinates every week during a month first, plants growth (high and leaf amount) every month after second month for 2 month. Research result indicates that treatment of land cover has an effect on reality to germination percentage, leaf amount, and high plants as for seedball diameter, seed amount and interaction between land cover and seedball diameter have an effect on reality to percentage of germination and leaf amount. Treatment of grass land cover gives influence is done well by germination percentage, leaf amount, and high plants. Seedball diameter 7,0 cm and seed amount 11 seeds give influence is done well by germination percentage. Combination of grass land cover treatment and diameter of seed ball 7,0 cm give best influence. Key words: Formulation, biological control agent, Aspergillus sp., and tablet.